IMPLEMENTASI KERJASAMA SISTER CITY BERDASARKAN VCLT 1969 (KASUS SISTER CITY KOTA BANDUNG DAN FORT WORTH): Implementation Of Sister City Cooperation Based On Vclt 1969 (Case Of Sister City In Bandung And Fort Worth) - Denyssa Jasmine Ardiansyah Putri; Andrey Sujatmoko (Reformasi Hukum Trisakti, 2025)
The practice of Sister City agreements is an agreement made by local governments between countries with the main purpose of improving friendly relations and providing benefits to the parties. The Sister City concept originated in the United States in 1956. Since 1990, Bandung City has been one of the leading cities in forming Sister City relationships, especially with Fort Worth City. Identification problem in this study is whether the implementation of the Sister City agreement between the Fort Worth City government and Bandung is in accordance with the principles of pacta sunt servanda and good faith. This research uses normative juridical research. This research uses a qualitative analysis approach by using library data that is analyzed in depth. The result research and conclusion is that the Sister City cooperation between the governments of Bandung and Fort Worth has been based on the commitment and principles of good faith and pacta sunt servanda based on the 1969 VCLT, this can be proven because for more than thirty years the two cities have consistently carried out this cooperation and felt many benefits from the cooperation.